Analysis of snackbar characteristic subtitute with banana flour var.raja nangka (musa paradisiaca) and mocaf flour - Prajwalita Rukmakharisma Rizki; Bowis Fatwa Afif; Dini Nadhilah; Dini Nurilmi Putri Suleman; Alfi Nur Rochmah; Fitriyah Zulfa; Yenny Febriana Ramdhan Abdi (Journal of Food and Agricultural Product, 2025)
Snack bars are bar-shaped and solid snacks, which can be categorized as healthy snacks because they contain complete nutrition, namely protein, carbohydrates, fiber, vitamins, and minerals. Snack bars are snacks that are usually eaten to delay hunger during meal times. It is made from flour mixed with cereals, nuts, dried fruits and oats. This research substitutes wheat flour with mocaf flour and banana flour (Musa paradisiaca). The aim is to reduce the use of wheat flour and empower the potential of local flour from cassava and add fiber. The addition of banana flour to provide different flavors and a longer satiety effect. Using the Completely Randomized Design (CRD) method with four formulations and three replications. Formulation P1 = control, P2 25% banana flour and 75% mocaf flour, P3 50% banana flour and 50% mocaf flour, P4 75% banana flour and 25% mocaf flour. The data obtained were analyzed using ANOVA (Analysis of Variance). The results of sensory testing showed that the best formulation was found in the snack bar sample with a formulation of 75% banana flour and 25% mocaf flour. The chemical characteristics of snack bars with substitutions of banana flour and mocaf flour are in the form of moisture content of 9.33%, ash content of 1.74%, protein content of 9.10%, fat content of 20.22, and crude fiber content of 92.58%.Keyword : snack bar, substitute, banana flour, mocaf flour